Successful Treatment of a COVID 19-Associated Multisystem Thrombotic Event in a Young Patient in a Neurocritical Care Unit - Lakshminarasimhaiah, Geetha; Rao, Ridhi (Journal of Neuroanaesthesiology and Critical Care, 2023)
This case report describes a young patient with no comorbidities, who presented with two systemic thrombotic events within 24 hours of admission. She presented with a right middle cerebral artery territory infarct and developed an inferior wall myocardial infarction soon after. The hypotension was refractory to inotropes and required emergency intra-aortic balloon pump insertion. She was evaluated for prothrombotic states and other causes of stroke in young. However, the workup for the same was negative. Coronavirus disease-2019 immunoglobulin G antibody titer and inflammatory markers were found to be extremely elevated, which suggested recent severe infection. This case report throws light on the multidisciplinary management of thrombotic events, most probably secondary to coronavirus infection.
Keywords: COVID-19; ischemic stroke; myocardial infarction